Economic evaluation of an acute paediatric hospital at home clinical trial. Issue 6 (1st December 2002) - Bagust, A; Haycox, A; Sartain, S A; Maxwell, M J; Todd, P
Abstract : Aims: To compare the privately borne and NHS costs of hospital at home (HAH) and conventional inpatient care for children with selected acute conditions. Methods: Prospective economic evaluation using cost minimisation analysis within a randomised controlled trial, in paediatric wards of a district general hospital, and private homes in the local catchment area in Wirral, Merseyside. Subjects were children who fulfilled the criteria for admission to HAH, suffering from breathing difficulties (n = 202), diarrhoea and vomiting (n = 125), or fever (n = 72). Results: Direct costs borne by families are reduced by 41% for HAH patients (£23.31 v £13.76, p = 0.001). There is no evidence that HAH transfers the burden of care to parents, and there is no difference in absence rates from paid employment. Patients and their carers expressed a strong preference for HAH. Comparison of NHS costs is equivocal, depending on how HAH is implemented alongside the conventional hospital service. Conclusion: Paediatric HAH schemes are unlikely to reduce NHS costs and do not increase privately borne costs. They will, however, significantly increase patient and carer satisfaction with care provision for sick children with appropriate conditions.